Effect of Chitosan on Meat Preservation - Purnama Darmadji; Masathoshi Izumimoto (Indonesian Food and Nutrition Progress, 1996)
The effect of chitosan as preservative on the qualities of meat including microbiological, chemical, sensory and color qualities were examined In liquid medium chitosan 0.01% inhibited the growth of some spoilage and pathogenic bacteria such as Bacillus subtilis, Escherichia coli, Pseudomonas fragi and Staphylococcus aureus. At 0.1% concentration it also inhibited the growth of meat starter cultures, Lactoba¬cillus plantarum, Pediococcus Pentosaceus and Micro-coccus varians. In meat, during incubation at 30°C for 48 hours or storage at 4°C for 10 days, chitosan inhib¬ited the growth of spoilage bacteria, reduced lipid oxi¬dation, putrefaction and resulted in better sensory test. Chitosan also had a good effect on the development of red color of meat during storage.